PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH PADA PROVINSI KEPULAUAN RIAU TAHUN 2013-2022 - Fauziah Nur; Zuwardi (ADISAM PUBLISHER, 2024)
Regional government financial performance will show the level of achievement of work results in the regional finance sector using the financial system through statutory policies during a certain period. So that regional governments are expected to be able to optimize the performance of the budget that is determined and approved. Regional government as one of the representatives of the central government in each region has a crucial role, especially related to the welfare of the people. Islam itself emphasizes that achieving prosperity that originates from public finances must be managed optimally for the needs and prosperity of increasing the benefit of the people. Thisresearch is motivated bythe lack of independence of regional governments, which shows that balancing fundsfrom the centralgovernment are greater than local original income. This shows that regional governments are stilldependent on thecentral government, which can result in a decline in regional government financial performance. In Islamic economics, humans are ordered to distribute their income so that it does not circulate to some people and avoid income disparities that can make poor people more miserable and rich people become richer. The results of this research show that Regional Original Income has a positive effect on local government financial performance, Balancing Funds has a negative effect on local government financial performance. Meanwhile, Regional Original Income and Balancing Funds have a significant effect on regional government financial performance